REVIEW TARGET DAN CAPAIAN INDEKS PEMBANGUNAN BIDANG SOSIAL KOTA MALANG TAHUN 2020 - Bidang Penelitian dan Pengembangan (Bappeda Kota Malang, 2021)
Review of government performance achievements is an annual agenda that must be carried out in accordance with the mandate of statutory regulations. not only that, the year 2020 requires the government to examine the impact of the pandemic against the targets that have been set. Malang City has 4 Missions in achieving its big vision, one of which is called the social development of Malang City. This study uses a multi-methods approach that allows researchers to use several research methods according to research needs. The results of this study indicate that the pandemic does not have a significant impact on the achievement of performance towards targets, both positive and negative impacts of damaging social development in Malang City. Some of the indicators used require special studies related to their significance to the above indicators so that from the program stage to sustainable goals according to the concept of Urban Sustainable Development.